URGENSI PERAN KELUARGA DALAM MEMBENTUK KARAKTER RELIGIUS ANAK DI ERA SOCIETY 5.0 - Anna Karma Yuhana (Damhil Education Journal, 2022)
The background of this research is that many parents are negligent and do not know how to carry out the task of educating and shaping children's character. Most mothers or fathers think that if the children have been handed over to the teacher at school, then their task of educating children is finished. Their job now is to earn money to pay for their children's schooling. Whereas the initial formation of character in a child when the child is in parental education.This study aims to determine the roles, strategies, challenges and expectations in shaping religious character in children in the era of society 5.0. This study uses a descriptive qualitative approach. Data collection techniques were carried out by interview, observation, and documentation. The data were analyzed using the Miles and Huberman model, which consisted of condensation data, display data, and drawing conclusions. The results of this study indicate that the role of the family in shaping children's character is as a foundation for religious and socio-cultural education, a place to grow affection and a place to learn. Family strategies in shaping children's religious character include: teaching, motivating, imitating, habituation. , rule enforcement. In shaping a child's religious character, it takes exemplary and habituation at home, for example, among others: getting used to being obedient in carrying out worship at home with the example of parents, getting used to setting aside some property to be given to others, getting used to saying kind and polite, getting used to covering aurat for girls and get used to reading the Qur'an at home. Challenges in shaping the character of children in the era of society 5.0 include: from the parents because of the busyness and lack of role models for children at home, limited time to study at school, the environment, and social media. While the hope is that children must be ready to face the challenges of the times, so that the expected generation is capable of critical thinking, has great curiosity, is open-minded (has broad insight), is creative and is able to become a problem solver.